Renal replacement therapy in the treatment and prevention of contrastinduced nephropathy after cardiovascular surgery - E. A. Tabakyan; A. E. Komlev; A. A. Margolina; R. S. Akchurin (Кардиоваскулярная терапия и профилактика)
Aim. To analyse the effectiveness of hemofiltration and high-volume hemodialysis for acute renal failure (ARF) prevention and treatment after cardiovascular surgery and contrast media (CM) use. Material and methods. The patients cardiovascular jurgery. For cardiovascular visualisation, low-osmolar or isoosmolar CM were used (ultravist, optiray and visipack, respectively). The risk of contrast-induced nephropathy (CIN) was assessed, according to the guidelines by Barrett ВJ, Parfrey PS (2006). Hemofiltration and high-volume hemodialysis (recirculating dialysate regimen) were performed with the Diapact®CRRT device, using the Duosol® solution. Heparin anticoagulation was monitored by activated coagulation time. Every 2-3 hours, the levels of hematocrit, potassium, sodium, glucose, pH, bicarbonate, and lactate in venous blood were measured. Results. Renal replacement therapy (RRT) procedures were performed in 5 patients after Stage III ARF development. In two cases, ARF was combined with multi-organ failure (MOF). In one case, ARF resulted in death, and in four other cases, ARF regressed with renal function normalisation. In one case of MOF, hyperbilirubinemia, and hyperenzymemia, hemofiltration was combined with plasmapheresis. In two patients with a very high ARF risk, hemofiltration and high-volume hemodialysis were performed preventatively, after cardiac surgery. Preventive RRT was not associated with a significant reduction in glomerular filtration rate (GFR) or with ARF development.Conclusion. In patients with CIN and ARF after CM use during angioplasty and hybrid cardiac surgery, RRT effectively reduces life-threatening metabolic complications of ARF. Among individuals with a very high ARF risk, RRT immediately after CM-using cardiovascular surgery can prevent a significant GFR reduction and ARF development.